Rasa Across Cultures: Applying Rasa Theory to Shakespearean Drama - Dibpriya Bodo (International Journal of Language and Literary Studies, 2025)
The present article explores the applicability of Bharata Muni’s rasa theory, as articulated in the Natyashastra, to the dramatic works of William Shakespeare, particularly his tragedies Othello, Hamlet, and Macbeth, and his late romances Cymbeline and The Tempest. While Western criticism, rooted in Aristotelian poetics, has traditionally emphasized structure, causality, and catharsis, later approaches, such as Marxist critique, foreground psychology or socio-political conflict. In contrast, rasa theory offers a distinct interpretive framework that privileges aesthetic experience and emotional universality. By closely analyzing Shakespeare’s plays through specific rasas, such as karuna (pathos), raudra (anger), srngara (love), soka (sorrow), and shanta (tranquility), among others, the study reveals how Shakespeare orchestrates not only narrative conflict but also deeply affects experiences that transcend historical and cultural contexts. Unlike Aristotelian catharsis, which purges emotions, rasa theory transforms them into shared aesthetic enjoyment, allowing audiences to savour universal sentiments beyond individual psychology or ideology. This comparative method demonstrates that Shakespeare’s art, when viewed through rasa, participates in a global aesthetics of emotion, situating his works within a broader intercultural dialogue that affirms the enduring power of drama to evoke beauty, wonder and transcendence.